Vilnius Editions from the End of the 16th and the Beginning of the 17th Century in Bulgaria - Polimirova, Mariya (Knygotyra, 2023)
The aim of this paper is to present the publications of the printing houses in Vilnius from the end of the 16th and the 17th century which have been preserved in the larger Bulgarian libraries and in the archives in Sofia, Plovdiv, and Rila Monastery. These are some of the liturgical books published by Peter Mstislavets, the Mamonichi brothers, and the printing house of the Holy Spirit Monastery. We are offering systematic information with brief descriptions of the preserved copies. We are tracing the distribution of these printed books and the ways of their penetration into the Bulgarian lands in the 16th –17th century, as well as their usage in the following centuries.